Economics of voluntary information sharing - José Liberti; Jason Sturgess; Andrew Sutherland (Queen Mary University of London, School of Economics and Finance, 2018)
We show that lenders join a U.S. commercial credit bureau when information asymmetries between incumbents and entrants create an adverse selection problem that hinders market entry. Lenders also delay joining when information asymmetries protect them from competition in existing markets, consistent with lenders trading off new market entry against heightened competition. We exploit shocks to information coverage to show that lenders enter new markets after joining the bureau in a pattern consistent with this trade-off. Our results illuminate why intermediaries voluntarily share information and show how financial technology that mitigates information asymmetries can shape the boundaries of lending.
Keywords: G21; G32; 330; information sharing; adverse selection; specialization; financial intermediation; collateral; credit bureaus; fintech